2020
DOI: 10.3390/su12229669
|View full text |Cite
|
Sign up to set email alerts
|

Working to Reduce Food Waste: Investigating Determinants of Food Waste amongst Taiwanese Workers in Factory Cafeteria Settings

Abstract: Food waste is a critical issue affecting the world, and more research is needed to find ways to reduce it. Much of the existing research has examined supply chain inefficiencies and plate waste in restaurants and homes, while few researchers have studied the food waste which occurs in factory cafeterias. As many factories are in Asia, examining factory cafeteria food waste behavior in an Asian context is a good starting point. With this in mind, the authors research drivers that influence Taiwanese factory wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
(125 reference statements)
0
10
1
Order By: Relevance
“…Bell's study (2020) reported a relationship between food waste and level of education [20]; on the opposite, no significant relationship was found between food waste and education level and frequency of attendance to the canteen in the present study, probably due to the homogeneity of participants' graduation level.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Bell's study (2020) reported a relationship between food waste and level of education [20]; on the opposite, no significant relationship was found between food waste and education level and frequency of attendance to the canteen in the present study, probably due to the homogeneity of participants' graduation level.…”
Section: Discussioncontrasting
confidence: 82%
“…Bell et al used the theory of planned behaviour (TPB) to analyze the influence of canteen workers' behavioral intentions toward food waste reduction. Loss of appetite, poor taste, low appeal, or lack of time to have meals presented a positive impact on food waste behavior [20]. The same TPB was used to analyze food waste behaviors in mass catering services and concluded that a greater intention not to leave edible food and a higher degree of perceived control over this behavior reduced the quantity of food waste [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some efforts have been made to expand attitude–behaviour models by including habits, often increasing the predictive power (e.g. Donald et al 2014 ; Chuang et al 2018 ; Bell and Ulhas 2020 ; Çoker and van der Linden 2020 ; Liu et al 2020 ; Aboelmaged 2021 ). Others call for more research on habits (Peattie 2010 ; Wynes et al 2018 ) or highlighting habits as a strong barrier/motivator for pro-environmental behaviours (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Extant studies have continued to endorse the essential role of habits on the behavior at play (Dang & Tran, 2020;Tuu, 2015). Some identified it as the most key predictor of behavior (Russell et al, 2017) and intention (Bell & Ulhas, 2020). Habit was confirmed to moderate the association between intention and behavior (de Bruijn et al, 2012;Gardner et al, 2012;Menozzi et al, 2021).…”
Section: Literature Review and Empirical Frameworkmentioning
confidence: 97%